The National Concept Behind Japanese Aesthetic "Wabi-sabi": Taking the Gold Ornaments in Nagoya City as an Example. - Mi, Lucheng (International Journal of Social Sciences and Public Administration, 2024)
This article takes the gold jewelry of Nagoya Castle as an example, and through a case study method, discusses the correlation between the Japanese aesthetic concept of "Wabi-sabi" and the social tradition of "gaman" and the philosophical thought of "no-self" in the Japanese national character. The purpose is to point out that aesthetic preferences are affected by external factors such as national growth environment and moral concepts. Similarly, Japanese philosophical thoughts and national concepts have had a profound impact on the formation and development of wabi-sabi aesthetics. The research in this article not only helps the academic community to fully grasp the essential characteristics of wabi-sabi aesthetics; it also helps the academic community to deeply understand the similarities and differences between wabi-sabi aesthetics and other aesthetic concepts; it has certain academic significance for promoting the theoretical research and practical application of wabi-sabi aesthetics and realistic value.